Mental health services in response to the COVID-19 pandemic in high-income countries: protocol for a rapid review - Yu Fu; Dawn Craig; Ge Yu (BMJ Open)
Introduction The COVID-19 pandemic has caused disruptions to mental health services, forcing the rapid implementation of alternative ways of delivering services alongside a greater immediate, and continuously growing, demand across those services. The care and level of mental health service provided are felt to be inadequate to respond to the increasing demand for mental health conditions in the time of the pandemic, leading to an urgent need to learn from service change and consequences to inform solutions and plans to support the NHS postpandemic plan in the UK. This rapid review aims to understand the changes in mental health services during the pandemic and summarise the impact of these changes on the health outcomes of people with mental health conditions.Methods and analysis Cochrane CENTRAL, MEDLINE, Embase and PsycInfo will be searched for eligible studies with key terms indicating mental health AND COVID-19 AND health services. Peer-reviewed empirical studies aiming to investigate or describe new models of care, services, initiatives or programmes developed or evolved for patients (aged 18 years or over) with mental health in response to COVID-19, published in the English language and undertaken in a high-income country defined by Organisation for Economic Co-operation and Development (OECD) member will be included. Studies reporting views of the general public, letters of opinion to peer-review journals, editorial or commentaries will be excluded. Study selection and data extraction will be undertaken independently by two reviewers. Evidence will be summarised narratively and in a logic model.Ethics and dissemination Ethics approval is not required for this review. A list of interventions/services/models of care delivered to people with mental health conditions will be grouped as ‘Do’, ‘Don’t’ and ‘Don’t know’ based on the evidence on effectiveness and acceptability. The results will be written for publication in an open-access peer-reviewed journal and disseminated to the public and patients, clinicians, commissioners, funders and academic conferences.PROSPERO registration number CRD42022306923.